Isothermal and non-isothermal cold crystallization of tetrabenzofluorene (TBF) molecules. (31st May 2019) - Boopathi, A. A.; Sampath, Srinivasan; Narasimhaswamy, T.
Abstract : Isothermal and non-isothermal cold crystallization of TBFC homologs is investigated by varying the alkyl chain length from C8 to C18 employing HOPM, DSC and powder XRD techniques. Abstract : Design and synthesis of tetrabenzo[ a, c, g, i ]fluorene (TBF) derivatives are carried out to investigate the isothermal and non-isothermal cold crystallization (CC) behavior by various spectroscopic and analytical techniques. The unprecedented CC exhibited by TBF molecules is examined by systematic modification of alkyl chain length (C8–C18 even carbons) on both sides of the central phenyl ring. The CC of the TBF derivatives is examined via hot-stage polarising microscopy (HOPM), differential scanning calorimetry (DSC) and variable temperature powder X-ray diffraction (VT-PXRD). The experimental observation reveals that with increase in alkyl chain length from C10 H21 to C16 H33, the CC temperature and the activation energy significantly increase. The non-isothermal CC activation energy is calculated using the Kissinger equation. By employing DSC kinetic parameters, the overall activation energies of the TBF molecules (TBFC10 to TBFC18) are calculated, which are in the range of 62.18–90.35 kJ mol −1 . Furthermore, the Avrami factors of the isothermal CC kinetics at five different temperatures are plotted, which indicates that with an increase in temperature the CC time is decreased.